Booker T. Washington Papers Volume 5 : 1899-1900. Assistant editor, Barbara S. Kraft - Washington, Booker T., 1856-1915 (Book collections on Project MUSE., 2015)
This volume turns from emphasizing Washington's institution-building (Tuskegee Institute) to examine those writings which reveal more about the black leader's growing role as a national public figure. Volume 5 covers a period during which Washington's fortunes continued to rise even as those of the black masses, for whom he claimed to speak, declined. Though forced to adhere narrowly to the racial philosophy he had espoused in the Atlanta Compromise address of 1895, Washington nonetheless was able to involve himself covertly in matters of civil rights and politics. He used the National Negro Business League as a front for political activity. He successfully lobbied against disenfranchisement of black voters in Georgia during November, 1899. During these years Washington began behind-the-scenes civil rights activities that foreshadowed a much more elaborate "secret life" after the turn of the century. He worked with lawyers of the Afro-American Council to test in the courts the grandfather clause of the Louisiana constitution of 1898, raising money to pay the legal costs and swearing the other participants to secrecy. T. Thomas Fortune, the leading black journalist of the day, was Washington's close personal advisor as he sought to spread his sphere of influence from his southern base to northern cities. Also included are writings on the first convention of the National Negro Business League, Washington's address before the Southern Industrial Convention in Huntsville, Ala., and the full text of Washington's first book, The Future of the American Negro, published in December, 1899.